Analisis Faktor yang Berhubungan dengan Kejadian Obesitas Mahasiswi FKM Uniska MAB Banjarmasin - Husnul Khatimatun Inayah; Netty Netty; Ari Widyarni; Nurul Indah Qariati; M. Bahrul Ilmi; Noorhidayah Noorhidayah (Jurnal Akademika Baiturrahim Jambi, 2026)
Obesity is a growing global nutrition problem, including in productive age groups such as college students. Female students, especially in the Faculty of Public Health (FKM), have a higher susceptibility to obesity due to lifestyle, hormonal and dietary factors. This study aims to analyze factors related to the incidence of obesity in FKM students of the Islamic University of Kalimantan MAB Banjarmasin. This study uses an analytical survey method with a cross sectional design. The study population was 1,370 FKM students, with a sample of 94 respondents determined using the Slovin formula (90% confidence level) and accidental sampling techniques. The variables studied included knowledge, frequency of Fast Food  consumption, and genetik factors, with data collection through questionnaires and Body Mass Index (BMI) measurements. Data analysis was carried out using the Chi Square test. The results showed the prevalence of obesity at 48.9%. Most of the respondents had sufficient knowledge (43.6%), often consumed Fast Food  (58.5%), and had a genetik history of obesity (55.3%). Bivariate analysis showed a significant relationship between knowledge (p=0.032), frequency of Fast Food  consumption (p=0.027), and genetiks (p=0.000) and the incidence of obesity in female students. The discussion of this study emphasizes that obesity in female students is not only influenced by lifestyle such as Fast Food  consumption, but also nutritional knowledge factors and genetik predisposition. College students with low knowledge are more prone to choosing high-calorie foods, while frequent consumption of Fast Food  contributes to excess energy. Genetik factors further strengthen the risk of obesity if it is not balanced with a healthy lifestyle. It is recommended that female students limit Fast Food  consumption and increase nutritional knowledge through health counseling. Further research is expected to add other variables, such as physical activity and stress, to enrich the analysis of obesity risk factors